2023
DOI: 10.5802/crgeos.154
|View full text |Cite
|
Sign up to set email alerts
|

The East-Mayotte new volcano in the Comoros Archipelago: structure and timing of magmatic phases inferred from seismic reflection data

Abstract: The East-Mayotte new volcano in the Comoros Archipelago: structure and timing of magmatic phases inferred from seismic reflection data Le nouveau volcan de l'Est-Mayotte dans l'archipel des Comores : structure et chronologie des phases magmatiques déduites des données d'imagerie sismique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…(b) Fani Maoré volcanic cone is located 50 km east from offshore Mayotte Island, at the end of the Eastern Volcanic Chain, as delineated by the white dashed lines [Bachèlery et al, 2021. a maximum age of 28 Ma for the onset of magmatic activity [Masquelet et al, 2022], recent volcanic activity has been documented both on land [possibly as young as 4 ka, Zinke et al, 2003] and on the distal part of a 60 km long WNW-ESE-oriented volcanic chain that extends 50 km off the eastern submarine flank of Mayotte up to the 2018-2021 Fani Maoré new edifice [Figure 1; Berthod et al, 2021b. Petite Terre, the eastern volcanic island of Mayotte, is characterized by the presence of recent volcanic activity [200 ka, Pelleter et al, 2014] ranging from older mafic Strombolian scoria cones to the younger well-preserved phonolitic tuff rings aligned on N140 trending fractures.…”
Section: Geological Settingmentioning
confidence: 99%
“…(b) Fani Maoré volcanic cone is located 50 km east from offshore Mayotte Island, at the end of the Eastern Volcanic Chain, as delineated by the white dashed lines [Bachèlery et al, 2021. a maximum age of 28 Ma for the onset of magmatic activity [Masquelet et al, 2022], recent volcanic activity has been documented both on land [possibly as young as 4 ka, Zinke et al, 2003] and on the distal part of a 60 km long WNW-ESE-oriented volcanic chain that extends 50 km off the eastern submarine flank of Mayotte up to the 2018-2021 Fani Maoré new edifice [Figure 1; Berthod et al, 2021b. Petite Terre, the eastern volcanic island of Mayotte, is characterized by the presence of recent volcanic activity [200 ka, Pelleter et al, 2014] ranging from older mafic Strombolian scoria cones to the younger well-preserved phonolitic tuff rings aligned on N140 trending fractures.…”
Section: Geological Settingmentioning
confidence: 99%
“…Sedimentation may affect heat flow by decreasing the temperature gradient as a function of the sedimentation rate [e.g., Manga et al, 2012]. Sedimentation rates are estimated at low values of 2-4 cm/1000 yr (Zaragosi, personal communication), comparable to values of 3 cm/1000 yr at IODP site U1476 [see inset Figure 1; Hall et al, 2017] and of 2-5 cm/1000 yr based on the thickness and estimated ages of sediment layers observed on seismic profiles from SISMAORE cruise [Thinon et al, 2022, Masquelet et al, 2022. Such low rates of sedimentation imply a negligible heat flow correction Uyeda, 1963, Manga et al, 2012].…”
Section: Methodsmentioning
confidence: 89%
“…The measurement is aligned with the eastern Volcanic Chain of Mayotte and located at the border of a recent forced fold, 10 km wide and 30 m high, underlain by a magmatic sill (Figure 3). Seismic reflection data from SISMAORE cruise show conduit-like features or chimneys within the sedimentary succession that may record the vertical migration of fluids towards the surface in the area [Masquelet et al, 2022]. Upward migration of hot fluids could be triggered by the renewed activity at the east Volcanic Chain of Mayotte, or by the recent sill intrusion that formed the forced fold.…”
mentioning
confidence: 99%
“…Flower, 1972, Roach et al, 2017, overlain by a thick sedimentary cover. Near Mayotte, the sedimentary cover reaches a thickness estimated at 1 to 2 km [Coffin et al, 1986], and more recently, at up to 3 km under the new eruption site [Masquelet et al, 2022]. From multichannel seismic reflection profiles, Malod et al [1991] identified N130°E trending structures within the Comoros Basin that are parallel to the movement of Madagascar with respect to the African Plate.…”
Section: Geological Settingmentioning
confidence: 99%
“…Interestingly, they lie at the southern tip of the distal seismic swarm which is interpreted as a feeder dyke [Figure 10, Feuillet et al, 2021, Retailleau et al, 2022. However there is so far no sign of seismic activity in the upper crust above 25 km depth, nor in the overlying first kilometers of the sedimentary cover [Coffin et al, 1986, Masquelet et al, 2022. The occurrence of this seismic cluster only between 25 and 50 km depth is still unexplained.…”
Section: Perspectivesmentioning
confidence: 99%